Conferences and societies / Konferensies en verenigings (Historia, 2021)
The VOC Foundation / Die Stigting VOC / Genealogical Society of South Africa / Genealogiese Genootskap van Suid-Afrika / International Oral History Association
Keywords: Genealogical Society of South Africa; Oral History; The VOC Foundation